Pengaruh Harga, Cita Rasa, Lokasi, Terhadap Keputusan Pembelian Pada Usaha Support Warmindo Kota Bengkulu - Anamica, Marshello; Irwanto, Tito; Fitriano, Yun; Melinda, Tri Febrina (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The purpose of this research is to determine the influence of price, taste and location on purchasing decisions at the Warmindo Support Business in Bengkulu City. This type of research is a type of quantitative research. The data collection method in this research used a questionnaire technique, with a sample of 100 respondents. The research results show that multiple linear regression Y = 21,967 + 0.141X1 + 0.312X2 + 0.129X3 + 3,943. Where the coefficient is positive, meaning that there is a positive or unidirectional relationship between the variables Price (X1), Taste (X2) Location (X3), the value is 0 (zero), Purchase Decision (Y) in the Warmindo Support business in Bengkulu City. The price test results (XI) show tcount 2,350 > ttable 1,984 and significance 0.021 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that price has a positive and significant effect on purchasing decisions at the Support Warmindo business in Bengkulu City. The results of the taste test (X2) show tcount 5.086 > ttable 1.984 and significance 0.000 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that taste has a positive and significant effect on purchasing decisions at the Support Warmindo business in Bengkulu City. The results of the location test (X3) show tcount 2.143> ttable 1.984 and significance 0.035 <0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that location has a positive and significant effect on purchasing decisions at the Support Warmindo business in Bengkulu City. Based on the comparison of the Fcount value with Ftable, the Fcount value is greater than the Ftable value, namely 13,821 > 2.47, so it is concluded that accepting the hypothesis, meaning that there is a simultaneous influence between price (XI), taste (X2), location (X3) on purchasing decisions at the Support Warmindo business in Bengkulu City. This can be seen at the significance level of 0.000 <0.05.